(untitled) (Applied Biological Research, 2013)
Cancer is one of the most devastating diseases that involves various cellular and genetic alternations and globally is 2nd leading cause of death in humans. Alternative medicines and their by-products provide a positive hope to manage cancer. However, non-specific bio-distribution and targeting, less water solubility, poor oral bio-availability and low therapeutic efficacy limit the pharmacological properties of conventional anti-cancer herbal drugs. In this review an attempt has been made to discuss about the mechanism and therapeutic efficacy of twenty different anti-cancerous herbal drugs with focus on their best utility. Different techniques of novel drug delivery systems (NDDS) like nano-particles, phyto-complex, liposome, ethosome, nano-emulsion and microsphere have been discussed as potential tools to remove various constraints associated with these herbal drugs. Various important issues related with novel drug carriers like their generalized mode of action, their potential advantages over conventional drugs, future opportunities, technological challenges and possible steps to patch up the existing gaps have been discussed.